2017
DOI: 10.1007/s11103-017-0591-y
|View full text |Cite
|
Sign up to set email alerts
|

In Arabidopsis thaliana distinct alleles encoding mitochondrial RNA PROCESSING FACTOR 4 support the generation of additional 5′ termini of ccmB transcripts

Abstract: In plant mitochondria, the 5' ends of many transcripts are generated post-transcriptionally. We show that the pentatricopeptide repeat (PPR) protein RNA PROCESSING FACTOR 4 (RPF4) supports the generation of extra 5' ends of ccmB transcripts in Landsberg erecta (Ler) and a number of other Arabidopsis thaliana ecotypes. RPF4 was identified in Ler applying a forward genetic approach supported by complementation studies of ecotype Columbia (Col), which generates the Ler-type extra ccmB 5' termini only after the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…In the reference accession Col‐0 of A. thaliana , 26 genes have been annotated as RFL PPRs and encode proteins predictively targeted to mitochondria, among which 20 are clustered on two loci of chromosome 1 (Fujii et al ., 2011). Today, only seven of these 26 genes have been studied: six are involved in post‐transcriptional processing of mitochondrial genes (Jonietz et al ., 2010, 2011; Hölzle et al ., 2011; Yang et al ., 2011; Arnal et al ., 2014; Stoll et al ., 2015, 2017; Fujii et al ., 2016) and one plays a critical role in seed germination (Yang et al ., 2011), but none of them has been shown to be involved in CMS.…”
Section: Introductionmentioning
confidence: 99%
“…In the reference accession Col‐0 of A. thaliana , 26 genes have been annotated as RFL PPRs and encode proteins predictively targeted to mitochondria, among which 20 are clustered on two loci of chromosome 1 (Fujii et al ., 2011). Today, only seven of these 26 genes have been studied: six are involved in post‐transcriptional processing of mitochondrial genes (Jonietz et al ., 2010, 2011; Hölzle et al ., 2011; Yang et al ., 2011; Arnal et al ., 2014; Stoll et al ., 2015, 2017; Fujii et al ., 2016) and one plays a critical role in seed germination (Yang et al ., 2011), but none of them has been shown to be involved in CMS.…”
Section: Introductionmentioning
confidence: 99%
“…Pentatricopeptide repeat (PPR) proteins form the largest family of proteins known to date that are directly involved in posttranscriptional modification in higher plants. Accumulating data indicate that PPR family members serve diverse functions in posttranscriptional modification, such as RNA editing (Ichinose & Sugita, ; Jiang et al ., ; Xiao et al ., ,b), RNA splicing (Ren et al ., ; Huang et al ., ; Tadini et al ., ), RNA processing (Rackham et al ., ; S. Wang et al ., ; Stoll et al ., ), RNA stability (Hammani et al ., ; Zoschke et al ., ; Y. Zhang et al ., ), RNA translation (Zhou et al ., ; Legen et al ., ), and RNA maturation (W. Wu et al ., ). The PPR gene family comprises 450 members in Arabidopsis and 477 members in rice (Saha et al ., ; Barkan & Small, ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, BnRFLs maintained a syntenic relationship with RFL genes in B. rapa and B. oleracea , suggesting that a conserved role of BnRFLs located on chromosomes A9 and C8. Moreover, AtRFL2 , AtRFL4 and AtRFL9 were located within the gene cluster on Arabidopsis chromosome 1 and participated in the processing of the mitochondrial RNA [ 25 27 ]. The phylogenetic analysis revealed that the BnRFLs have the closer phylogenetic relationship with AtRFLs and RsRFLs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…AtRFL4 is needed for processing the 5′-end of nad4 mRNA in mitochondria [ 26 ]. AtRFL9, also known as RNA PROCESSING FACTOR 4 (RPF4), participates in the generation of extra 5′ termini of ccmB transcripts in Arabidopsis [ 27 ]. These results enhanced our understanding of mitochondrial RNA processing in plants and provided novel insights into the function of RFL proteins.…”
Section: Introductionmentioning
confidence: 99%